The consumption-income ratio, entrepreneurial Rrisk and the US stock market: Technical appendix - Mathias Hoffmann (University of Zurich, Department of Economics, 2014)
This appendix is for publication as supplementary web-material only. The main article will appear in the Journal of Money, Credit and Banking.
Keywords: 330